Transcriptional and epigenetic control of cell fate decisions in early embryos - Alberio, Ramiro (CSIRO Publishing, 2017)
Mammalian embryo development is characterized by regulative mechanisms of lineage segregation and cell specification. A combination of carefully orchestrated gene expression networks, signalling pathways and epigenetic marks define specific developmental stages that can now be resolved at the single-cell level. These new ways to depict developmental processes have the potential to provide answers to unresolved questions on how lineage allocation and cell fate decisions are made during embryogenesis. Over the past few years, a flurry of studies reporting detailed single-cell transcription profiles in early embryos has complemented observations acquired using live-cell imaging following gene editing techniques to manipulate specific genes. The adoption of this newly available toolkit is reshaping how researchers are designing experiments and how they view animal development. This review presents an overview of the current knowledge on lineage segregation and cell specification in mammals, and discusses some of the outstanding questions that current technological advances can help scientists address, like never before.